Rongjin Niantong Fang ameliorates cartilage degeneration by regulating the SDF-1/CXCR4-p38MAPK signalling pathway - Jun Chen; Nan Chen; Ting Zhang; Jie Lin; Yunmei Huang; Guangwen Wu (Taylor & Francis Group, 2022)
AbstractContext Rongjin Niantong Fang (RJNTF) is a Traditional Chinese Medicine formulation with a good therapeutic effect on osteoarthritis (OA). However, the underlying mechanisms remain unclear.Objective This study investigates whether RJNTF could delay OA cartilage degeneration by regulating the SDF-1/CXCR4-p38MAPK signalling pathway.Materials and methods The Sprague-Dawley (SD) rats were used to establish the OA model by a modified Hulth's method. SD rats were divided into three groups (n = 10): blank group, model group (0.9% saline, 10 mL/kg/day), and treatment group (RJNTF, 4.5 g/kg/day). After 12 weeks of treatment, each group was analysed by H&E, Safranine-O solid green, ELISA, Immunohistochemistry, and Western blot. An in vitro model was induced with 100 ng/mL SDF-1 by ELISA, the blank group, model group, RJNTF group, and inhibitor group with intervention for 12 h, each group was analysed by Immunofluorescence staining and Western blot.Results SDF-1 content in the synovium was reduced in RJNTF treatment group compared to non-treatment model group (788.10 vs. 867.32 pg/mL) and down-regulation of CXCR4, MMP-3, MMP-9, MMP-13 protein expression, along with p38 protein phosphorylated were observed in RJNTF treatment group. In vitro results showed that RJNTF (IC50 = 8.925 mg/mL) intervention could down-regulate SDF-1 induced CXCR4 and p38 protein phosphorylated and reduce the synthesis of MMP-3, MMP-9, and MMP-13 proteins of chondrocytes from SD rat cartilage tissues.Discussion and conclusion RJNTF alleviates OA cartilage damage by SDF-1/CXCR4-p38MAPK signalling pathway inhibition. Our ongoing research focuses on Whether RJNTF treats OA through alternative pathways.